Accuracy of MRI-Compatible Contrast Media Injectors - Saake, Marc; Wüst, Wolfgang; Becker, Stefan; Uder, Michael; Janka, Rolf Matthias (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To analyze the exactness of MRI-compatible contrast media (CM) injectors in an experimental setup and clinical use. Materials and Methods: Ejected fluid volumes and amounts of CM were quantified for single and double piston injections. The focus was on small volumes, as used in pediatric examination and test-bolus measurements. Samples were collected before and after clinical MRI scans and amounts of CM were measured. Results: For single piston injections the volume differences were minimal (mean difference 0.01 ml). For double piston injections the volume of the first injection was decreased (mean 20.74 ml, target 21.00 ml, p < 0.01). After a position change of the Y-piece of the injection system, the amount of CM differed significantly from the target value (mean 1.23 mmol and 0.83 mmol at 1 ml/s flow rate, target 1.00 mmol, p < 0.01), independently of the wait time. The clinical samples confirmed these findings. Conclusion: The pistons of modern CM injectors work exactly. However, for small CM volumes the injected amount of CM can differ significantly from the target value in both directions. Influence factors are an incomplete elimination of air and exchange processes between the CM and saline chaser in the injection system. Key Points: o?In MRI examinations of children and test-bolus measurements, small amounts of CM are used.o?The accuracy of single piston injections is high.o?In double piston injections the injected amount of CM can differ significantly from the target value. Citation Format: o?Saake M, Wuest W, Becker S et al. Genauigkeit von MRT-kompatiblen Kontrastmittelinjektoren. Fortschr Röntgenstr 2014; 186: 253 - 259.
EVALuna2:14348

A mixed waveform protocol for reduction of the cardiac motion artifact in black-blood diffusion-weighted imaging of the liver - Rauh, Susanne S.; Riexinger, Andreas; Ohlmeyer, Sabine; Hammon, Matthias; Saake, Marc; Stemmer, Alto; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd (Magnetic Resonance Imaging, 2020)
Objective: Diffusion-weighted imaging (DWI) in the liver suffers from signal loss due to the cardiac motion artifact, especially in the left liver lobe. The purpose of this work was to improve the image quality of liver DWI in terms of cardiac motion artifact reduction and achievement of black-blood images in low b-value images. Material and methods: Ten healthy volunteers (age 20–31 years) underwent MRI examinations at 1.5 T with a prototype DWI sequence provided by the vendor. Two diffusion encodings (i.e. waveforms), monopolar and flow-compensated, and the b-values 0, 20, 50, 100, 150, 600 and 800 s/mm2 were used. Two Likert scales describing the severity of the pulsation artifact and the quality of the black-blood state were defined and evaluated by two experienced radiologists. Regions of interest (ROIs) were manually drawn in the right and left liver lobe in each slice and combined to a volume of interest (VOI). The mean and coefficient of variation were calculated for each normalized VOI-averaged signal to assess the severity of the cardiac motion artifact. The ADC was calculated using two b-values once for the monopolar data and once with mixed data, using the monopolar data for the small and the flow-compensated data for the high b-value. A Wilcoxon rank sum test was used to compare the Likert scores obtained for monopolar and flow-compensated data. Results: At b-values from 20 to 150 s/mm2, unlike the flow-compensated diffusion encoding, the monopolar encoding yielded black blood in all images with a negligible signal loss due to the cardiac motion artifact. At the b-values 600 and 800 s/mm2, the flow-compensated encoding resulted in a significantly reduced cardiac motion artifact, especially in the left liver lobe, and in a black-blood state. The ADC calculated with monopolar data was significantly higher in the left than in the right liver lobe. Conclusion: It is recommendable to use the following mixed waveform protocol: Monopolar diffusion encodings at small b-values and flow-compensated diffusion encodings at high b-values.
CRIS-Team Scopus Importer:2020-01-21

Angiographic CT with intravenous contrast agent application for monitoring of intracranial flow diverting stents - Saake, Marc; Struffert, Tobias; Gölitz, Philipp; Ott, Sabine; Seifert, Frank; Ganslandt, Oliver; Dörfler, Arnd (Neuroradiology, 2012)
Introduction: Intracranial flow diverting devices are increasingly used to treat cerebral aneurysms. A reliable, noninvasive follow-up modality would be desirable. Our aim was to compare intra-arterial digital subtraction angiography (ia DSA) to angiographic computed tomography with intravenous contrast agent application (iv ACT) in the visualisation of flow diverting devices and aneurysm lumina. Methods: Follow-up monitoring by iv ACT (n=36) and ia DSA (n=25) in 14 patients treated with flow diverting devices for intracranial aneurysms was evaluated retrospectively. Images were evaluated by two neuroradiologists in anonymous consensus reading regarding the device deployment, wall apposition, neck coverage of the aneurysm, opacification of the vessel and device lumen, as well as the degree of aneurysm occlusion. Results: Corresponding ia DSA and iv ACT images were scored identically in all patients regarding the stent deployment, wall apposition and neck coverage, as well as the degree of aneurysm occlusion and patency status of the device and parent artery. Opacification of the parent vessel lumen and perfused parts of the aneurysm was considered slightly inferior for iv ACT in comparison with ia DSA (seven of 36 cases), without impact on diagnosis. Conclusions: We demonstrated the feasibility and diagnostic value of iv ACT in follow-up imaging of intracranial flow diverting devices. Due to its high spatial resolution and non-invasive character, this novel technique might become a valuable imaging modality in these patients. © Springer-Verlag 2011.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiography; Computed tomography; Flat detector; Flow diverting stent; Follow-up; Intravenous

Angiographic CT with intravenous contrast injection compared with conventional rotational angiography in the diagnostic work-up of cerebral aneurysms - Gölitz, Philipp; Struffert, Tobias; Knossalla, F.; Saake, Marc; Ott, Sabine; Ganslandt, Oliver; Dörfler, Arnd (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: Noninvasive imaging of cerebral aneurysms is still considered inferior to conventional angiography. The purpose of this study was to evaluate the diagnostic accuracy of ivACT in the assessment of intracranial aneurysms compared with 3D-DSA. MATERIALS AND METHODS: We included 13 patients with 15 incidental unruptured saccular aneurysms scheduled for diagnostic angiographic work-up in our study. In each patient, we performed an ivACT and a conventional angiography including a 3D rotational run. During postprocessing, MPR images were generated for each technique. Maximal aneurysm diameter, neck diameter, aneurysm height, maximum width, bulge height, parent artery diameter, and angle between the parent artery and aneurysm apex were measured for each aneurysm. RESULTS: 3D-DSA and ivACT both provided images of high quality without artificial disturbances (ie, motion artifacts). Measurements of all parameters resulted in comparable values for both modalities with a strong correlation (P ≤ .001). CONCLUSIONS: ivACT is feasible for the noninvasive visualization of saccular cerebral aneurysms and may provide reliable diagnostic information for the assessment of aneurysm size and geometry comparable with conventional intra-arterial 3D rotational angiography. These preliminary results might be a first promising step to replacing conventional angiography in preinterventional aneurysm imaging.
CRIS-Team Scopus Importer:2022-08-05

Association of brain functional magnetic resonance activity with response to tumor necrosis factor inhibition in rheumatoid arthritis - Rech, Jürgen; Heß, Andreas; Finzel, Stephanie; Kreitz, Silke; Sergeeva, Marina; Englbrecht, Matthias; Dörfler, Arnd; Saake, Marc; Schett, Georg (Arthritis and Rheumatism, 2013)
Objective To test whether brain activity predicts the response to tumor necrosis factor inhibitors (TNFi) in patients with rheumatoid arthritis (RA). Since clinical and laboratory parameters have proven unsuccessful in predicting response, we followed a radically different concept, hypothesizing that response to TNFi depends on central nervous system activity rather than the clinical signs of disease. Methods Sequential testing by functional magnetic resonance imaging (MRI) of the brain, anatomic MRI of the hand, and clinical assessment of arthritis were carried out in 10 patients with active RA before and 3, 7, and 28 days after the start of TNFi treatment. Results Baseline demographic and disease-specific parameters were identical in TNFi responders and nonresponders. The mean ± SEM decrease in the Disease Activity Score in 28 joints after 28 days was -1.8 ± 0.3 in TNFi responders (n = 5) and -0.2 ± 0.1 in nonresponders (n = 5). Responders showed significantly higher baseline activation in thalamic, limbic, and associative areas of the brain than nonresponders. Moreover, brain activity decreased within 3 days after TNFi exposure in the responders, preceding clinical responses (day 7) and responses observed on the anatomic hand MRI (day 28). Conclusion These data suggest that response to TNFi depends on brain activity in RA patients, reflecting the subjective perception of disease. Copyright © 2013 by the American College of Rheumatology.
CRIS-Team Scopus Importer:2021-02-03

Automated tube voltage adaptation in head and neck computed tomography between 120 and 100 kV: effects on image quality and radiation dose - May, Matthias; Kramer, Manuel; Eller, Achim; Wüst, Wolfgang; Scharf, Michael; Brand, Michael; Saake, Marc; Schmidt, Bernhard; Uder, Michael; Lell, Michael (Neuroradiology, 2014)
Low tube voltage allows for computed tomography (CT) imaging with increased iodine contrast at reduced radiation dose. We sought to evaluate the image quality and potential dose reduction using a combination of attenuation based tube current modulation (TCM) and automated tube voltage adaptation (TVA) between 100 and 120 kV in CT of the head and neck.One hundred thirty consecutive patients with indication for head and neck CT were examined with a 128-slice system capable of TCM and TVA. Reference protocol was set at 120 kV. Tube voltage was reduced to 100 kV whenever proposed by automated analysis of the localizer. An additional small scan aligned to the jaw was performed at a fixed 120 kV setting. Image quality was assessed by two radiologists on a standardized Likert-scale and measurements of signal- (SNR) and contrast-to-noise ratio (CNR). Radiation dose was assessed as CTDIvol.Diagnostic image quality was excellent in both groups and did not differ significantly (p = 0.34). Image noise in the 100 kV data was increased and SNR decreased (17.8/9.6) in the jugular veins and the sternocleidomastoid muscle when compared to 120 kV (SNR 24.4/10.3), but not in fatty tissue and air. However, CNR did not differ statistically significant between 100 (23.5/14.4/9.4) and 120 kV data (24.2/15.3/8.6) while radiation dose was decreased by 7-8%.TVA between 100 and 120 kV in combination with TCM led to a radiation dose reduction compared to TCM alone, while keeping CNR constant though maintaining diagnostic image quality.
EVALuna2:14375

Blockade of TNF-α rapidly inhibits pain responses in the central nervous system - Heß, Andreas; Axmann, Roland; Rech, Jürgen; Finzel, Stephanie; Heindl-Erdmann, Cornelia; Kreitz, Silke; Sergeeva, Marina; Saake, Marc; Garcia, Meritxell; Kollias, George; Straub, Rainer H.; Sporns, Olaf; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
There has been a consistent gap in understanding how TNF-α neutralization affects the disease state of arthritis patients so rapidly, considering that joint inflammation in rheumatoid arthritis is a chronic condition with structural changes. We thus hypothesized that neutralization of TNF-α acts through the CNS before directly affecting joint inflammation. Through use of functional MRI (fMRI), we demonstrate that within 24 h after neutralization of TNF-α, nociceptive CNS activity in the thalamus and somatosensoric cortex, but also the activation of the limbic system, is blocked. Brain areas showing blood-oxygen level-dependent signals, a validated method to assess neuronal activity elicited by pain, were significantly reduced as early as 24 h after an infusion of a monoclonal antibody to TNF-α. In contrast, clinical and laboratory markers of inflammation, such as joint swelling and acute phase reactants, were not affected by anti-TNF-α at these early time points. Moreover, arthritic mice overexpressing human TNF-α showed an altered pain behavior and amore intensive, widespread, and prolonged brain activity upon nociceptive stimuli compared with wild-type mice. Similar to humans, these changes, as well as the rewiring of CNS activity resulting in tight clustering in the thalamus, were rapidly reversed after neutralization of TNF-α. These results suggest that neutralization of TNF-α affects nociceptive brain activity in the context of arthritis, long before it achieves antiinflammatory effects in the joints.
CRIS-Team Scopus Importer:2021-02-03
Keywords: Antiinflammatory therapy; Cytokines

Brain correlates of short-term habituation to repetitive electrical noxious stimulation - Nickel, Franziska; Ott, Sabine; Möhringer, Susanne; Saake, Marc; Dörfler, Arnd; Seifert, Frank; Maihöfner, Christian (European Journal of Pain, 2014)
Habituation to repetitive noxious stimuli is a well-known phenomenon. We investigated brain correlates of habituation to pain in a transdermal electrical pain model using functional magnetic resonance imaging (fMRI).Electrical painful stimulation with 1 Hz was applied to the volar forearm of 48 healthy subjects for 45 min. Before and after conditioning stimulation, psychophysical testing and fMRI were performed. During fMRI sessions, the subjects underwent blockwise painful electrical stimulation with a fixed percept-adapted current intensity. After fMRI 1 and fMRI 2 subjects rated the individual pain intensity of the electrical stimulus.Substantial habituation occurred during conditioning electrical stimulation. Accordingly, areas typically involved in pain processing showed decreased activity after conditioning stimulation. The blood oxygen level-dependent signal of the subgenual anterior cingulate gyrus, the superior parietal lobule and the supplemental motor area correlated positively with habituation. In contrast, activity in the periaqueductal grey, thalamus and insula correlated negatively. The results of the correlation analyses did not survive correction for multiple comparisons.With this study, we identified central components associated with habituation to repetitive painful stimuli. The results suggest that an increase in tonic inhibitory activity in cortical pain processing areas is a major mechanism contributing to habituation to phasic noxious stimuli. Moreover, areas involved in descending pain modulation were differentially modulated. This may hint at a simultaneous activation of facilitating and inhibiting nociceptive systems that are both altered in the transdermal electrical pain model.
EVALuna2:14468

Carotid CTA at the Lowest Tube Voltage (70 kV) in Comparison with Automated Tube Voltage Adaption - Eller, A.; Wiesmüller, Marco; Wüst, Wolfgang; Heiß, Rafael; Kopp, Markus; Saake, Marc; Brand, Michael; Uder, Michael; May, Matthias (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: CTA is the imaging modality of choice in many institutions for the evaluation of the supraaortic vessels, but radiation exposure remains a matter of concern. Our aim was to evaluate a 70-kV protocol for CT angiography of the carotid arteries with respect to image quality and radiation exposure compared with automated tube voltage adaption. MATERIALS AND METHODS: A total of 90 consecutive patients were included in this prospective study and randomized to the study group (n = 45, 70 kV) or control group (n = 45, automated tube voltage adaptation). Volume CT dose indices and dose-length products were recorded in the examination protocol. Image quality was assessed as arterial vessel contrast, signal-to-noise ratio, contrast-to-noise ratio, and contrast-to-noise ratio in reference to the radiation dose. Subjective overall image-quality analysis, image-artifact analysis, and diagnostic evaluation were performed by 2 observers by using a 4-point Likert scale. RESULTS: Radiation exposure was significantly lower in the study group (volume CT dose index reduced by 22%, dose-length product reduction by 20%; each P < .001). Contrast (P = .15), SNR (P = .4), and contrast-to-noise ratio (P = .5) did not show significant differences between the groups. The contrast-to-noise ratio in reference to the radiation dose was not significantly increased using the study protocol (P = .2). Subjective image quality and visualization of pathologic findings did not differ significantly between the groups. CONCLUSIONS: Carotid CTA using the lowest available voltage (70 kV) is feasible at very-low-dose levels, while overall image quality is comparable with protocols using automated tube voltage selection.
CRIS-Team Scopus Importer:2019-09-03

Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
Contradictory results were reported for the outcome after endovascular recanalization (ERT) in acute anterior circulation ischemic stroke. We assessed whether a clinical/perfusion CT cerebral blood volume (CBV) mismatch concept (CPM) can identify patients who will benefit from reperfusion therapy.Imaging and clinical data of 58 consecutive ERT cases with acute anterior circulation stroke (ICA, M1, proximal M2) undergoing intraarterial thrombectomy within 4.5h after symptom onset were analyzed retrospectively. CPM was defined as NIHSS>=8 and PCT CBV ASPECTS>=7. Minor CBV lesion was defined as PCT CBV ASPECTS>=7.All baseline characteristics other than blood glucose did not differ between the paired groups. Revascularization was achieved in 87.9% of all patients without significant difference between the paired groups. Favorable clinical outcome after 3 months (mRS<=2) resulted in 29.3% of all patients, in contrast to 47.4% of the CPM positive and 52.2% of the minor CBV lesion groups.CPM can identify patients who will benefit from reperfusion therapy in acute anterior circulation ischemic stroke.
EVALuna2:14386

Comparison of conventional CTA and volume perfusion CTA in evaluation of cerebral arterial vasculature in acute stroke - Saake, Marc; Gölitz, Philipp; Struffert, Tobias; Breuer, Lorenz; Volbers, Bastian; Dörfler, Arnd; Kloska, Stephan (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: CTA-like datasets can be reconstructed from whole-brain VPCTA. The aim of our study was to compare VPCTA with CTA for detection of intracranial stenosis and occlusion in stroke patients. Omitting CTA from stroke CT could reduce radiation dose. MATERIALS AND METHODS: One hundred sixty-three patients were included in this retrospective analysis. Inclusion criterion was suspected stroke within 4.5 hours after onset of symptoms. All examinations were performed on a 128-section multidetector CT scanner. Axial, coronal, and sagittal maximum intensity projections were reconstructed from CTA and from peak arterial phase of VPCTA. Images were scored for quality and presence of intracranial stenosis >50% or occlusion. For statistical analysis, the Wilcoxon signed-rank test and Fisher exact test were used, with a 2-tailed P value of .05 or less for statistical significance. RESULTS: Average image quality was superior in CTA (P < .05). However, image quality dichotomized for diagnostic significance was without difference between CTA and VPCTA (P > .05). Comparative statistical analysis revealed no significant difference for detection of intracranial stenosis and occlusion between CTA and VPCTA (P > .05). Substitution of intracranial CTA by VPCTA would lower radiation dose by 0.5 mSv. CONCLUSIONS: VPCTA is suited to assess the intracranial vasculature in patients with stroke and might have the potential to decrease radiation dose by substituting for intracranial CTA in stroke CT. Additional studies are necessary to further evaluate potential benefits of the dynamic nature of VPCTA.
CRIS-Team Scopus Importer:2022-08-05

Comparison of Readout-Segmented Echo-Planar Imaging and Single-Shot TSE DWI for Cholesteatoma Diagnostics - Wiesmüller, Marco; Wüst, Wolfgang; May, Matthias; Ellmann, Stephan; Heiß, Rafael; Saake, Marc; Janka, Rolf Matthias; Uder, Michael; Laun, Frederik Bernd (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: The high diagnostic value of DWI for cholesteatoma diagnostics is undisputed. This study compares the diagnostic value of readout-segmented echo-planar DWI and single-shot TSE DWI for cholesteatoma diagnostics.
CRIS-Team WoS Importer:2021-06-04

Computer-aided diagnosis in multiparametric mri of the prostate: An open-access online tool for lesion classification with high accuracy - Ellmann, Stephan; Schlicht, Michael; Dietzel, Matthias; Janka, Rolf Matthias; Hammon, Matthias; Saake, Marc; Ganslandt, Thomas; Hartmann, Arndt; Kunath, Frank; Wullich, Bernd; Uder, Michael; Bäuerle, Tobias (Cancers, 2020)
Computer-aided diagnosis (CADx) approaches could help to objectify reporting on prostate mpMRI, but their use in many cases is hampered due to common-built algorithms that are not publicly available. The aim of this study was to develop an open-access CADx algorithm with high accuracy for classification of suspicious lesions in mpMRI of the prostate. This retrospective study was approved by the local ethics commission, with waiver of informed consent. A total of 124 patients with 195 reported lesions were included. All patients received mpMRI of the prostate between 2014 and 2017, and transrectal ultrasound (TRUS)-guided and targeted biopsy within a time period of 30 days. Histopathology of the biopsy cores served as a standard of reference. Acquired imaging parameters included the size of the lesion, signal intensity (T2w images), diffusion restriction, prostate volume, and several dynamic parameters along with the clinical parameters patient age and serum PSA level. Inter-reader agreement of the imaging parameters was assessed by calculating intraclass correlation coefficients. The dataset was stratified into a train set and test set (156 and 39 lesions in 100 and 24 patients, respectively). Using the above parameters, a CADx based on an Extreme Gradient Boosting algorithm was developed on the train set, and tested on the test set. Performance optimization was focused on maximizing the area under the Receiver Operating Characteristic curve (ROCAUC). The algorithm was made publicly available on the internet. The CADx reached an ROCAUC of 0.908 during training, and 0.913 during testing (p = 0.93). Additionally, established rule-in and rule-out criteria allowed classifying 35.8% of the malignant and 49.4% of the benign lesions with error rates of <2%. All imaging parameters featured excellent inter-reader agreement. This study presents an open-access CADx for classification of suspicious lesions in mpMRI of the prostate with high accuracy. Applying the provided rule-in and rule-out criteria might facilitate to further stratify the management of patients at risk.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Artificial intelligence; Computer-aided diagnosis; Machine learning; Prostate cancer; Prostate mpMRI

Cone beam CT imaging of the paranasal region with a multipurpose X-ray system-image quality and radiation exposure - Ohlmeyer, Sabine; Saake, Marc; Buder, Thomas; May, Matthias; Uder, Michael; Wüst, Wolfgang (Applied Sciences, 2020)
Besides X-ray and fluoroscopy, a previously introduced X-ray scanner offers a 3D cone beam option (Multitom Rax, Siemens Healthcare). The aim of this study was to evaluate various scan parameters and post-processing steps to optimize image quality and radiation exposure for imaging of the parasinus region. Four human cadaver heads were examined with different tube voltages (90-121 kV), dose levels (DLs) (278-2180 nGy) and pre-filtration methods (none, Cu 0.2 mm, Cu 0.3 mm and Sn 0.4 mm). All images were reconstructed in 2 mm slice thickness with and without a metal artifact reduction algorithm in three different kernels. In total, 80 different scan protocols and 480 datasets were evaluated. Image quality was rated on a 5-point Likert scale. Radiation exposure (mean computed tomography volume index (CTDIvol) and effective dose) was calculated for each scan. The most dose-effective combination for the diagnosis of sinusitis was 121 kV/DL of 278/0.3 mm copper (CTDIvol 1.70 mGy, effective dose 77 μSv). Scan protocols with 121 kV/DL1090/0.3 mm copper were rated sufficient for preoperative sinus surgery planning (CTDIvol 4.66 mGy, effective dose 212 μSv). Therefore, sinusitis and preoperative sinus surgery planning can be performed in diagnostic image quality at low radiation dose levels with a multipurpose X-ray system.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Computed tomography; DVT; Medical imaging; Parasinus region; Sinusitis; Three-dimensional; X-ray

Contrast medium application in pediatric high-pitch cardiovascular CT angiography: manual or power injection? - Saake, Marc; Lell, Michael; Rompel, Oliver; Glöckler, Martin; May, Matthias; Eller, Achim; Achenbach, Stephan; Uder, Michael; Wüst, Wolfgang (Journal of Cardiovascular Computed Tomography, 2014)
Dual-source CT offers accurate depiction of cardiac structures in children with congenital heart disease. For cardiac CT, optimal enhancement of the cardiovascular structures is essential. There is considerable controversy about the administration of contrast medium (CM) in infants and small children, with either a power injector or a manual (hand) injection.The aim of this study was to compare image quality with power injection of CM (study group) and manual injection (control group).Thirty-four patients (study group, 6.8 ± 9.6 months and control group, 4.6 ± 8.9 months, nonrandomized) underwent dual-source CT angiography of the chest using a prospective electrocardiography-triggered high-pitch spiral mode (pitch, 3.4; 80 kV). In the study group (17 patients), a power injector was used, and in the control group (17 patients, historical group), manual CM injection had been performed. To assess image quality, both subjective and objective parameters were evaluated independently by 2 experienced radiologists.Subjective overall image quality, signal-to-noise ratio, and contrast-to-noise ratio were significantly higher using power injection compared with manual injection (P < .05). However, depiction of cardiovascular structures did not differ significantly between both groups in all evaluated regions except the superior vena cava and the coronary arteries.In infants and small children with congenital heart disease, both manual and power injector protocols allowed for diagnostic imaging of cardiac and extracardiac structures. However, image quality and vascular attenuation were superior using a power injector.
EVALuna2:11950

Cutting Staff Radiation Exposure and Improving Freedom of Motion during CT Interventions: Comparison of a Novel Workflow Utilizing a Radiation Protection Cabin versus Two Conventional Workflows - Dankerl, Peter; May, Matthias; Canstein, Christian; Uder, Michael; Saake, Marc (Diagnostics, 2021)
This study aimed to evaluate the radiation exposure to the radiologist and the procedure time of prospectively matched CT interventions implementing three different workflows-the radiologist-(I) leaving the CT room during scanning; (II) wearing a lead apron and staying in the CT room; (III) staying in the CT room in a prototype radiation protection cabin without lead apron while utilizing a wireless remote control and a tablet. We prospectively evaluated the radiologist's radiation exposure utilizing an electronic personal dosimeter, the intervention time, and success in CT interventions matched to the three different workflows. We compared the interventional success, the patient's dose of the interventional scans in each workflow (total mAs and total DLP), the radiologist's personal dose (in mu SV), and interventional time. To perform workflow III, a prototype of a radiation protection cabin, with 3 mm lead equivalent walls and a foot switch to operate the doors, was built in the CT examination room. Radiation exposure during the maximum tube output at 120 kV was measured by the local admission officials inside the cabin at the same level as in the technician's control room (below 0.5 mu Sv/h and 1 mSv/y). Further, to utilize the full potential of this novel workflow, a sterile packed remote control (to move the CT table and to trigger the radiation) and a sterile packed tablet anchored on the CT table (to plan and navigate during the CT intervention) were operated by the radiologist. There were 18 interventions performed in workflow I, 16 in workflow II, and 27 in workflow III. There were no significant differences in the intervention time (workflow I: 23 min +/- 12, workflow II: 20 min +/- 8, and workflow III: 21 min +/- 10, p = 0.71) and the patient's dose (total DLP, p = 0.14). However, the personal dosimeter registered 0.17 +/- 0.22 mu Sv for workflow II, while I and III both documented 0 mu Sv, displaying significant difference (p < 0.001). All workflows were performed completely and successfully in all cases. The new workflow has the potential to reduce interventional CT radiologists' radiation dose to zero while relieving them from working in a lead apron all day.
CRIS-Team WoS Importer:2021-07-09

Deep Learning-Guided Weighted Averaging for Signal Dropout Compensation in DWI of the Liver - Gadjimuradov, Fasil; Benkert, Thomas; Nickel, Marcel Dominik; Führes, Tobit; Saake, Marc; Maier, Andreas (Magnetic Resonance in Medicine, 2022)
Purpose To develop an algorithm for the retrospective correction of signal dropout artifacts in abdominal DWI resulting from cardiac motion. Methods Given a set of image repetitions for a slice, a locally adaptive weighted averaging is proposed that aims to suppress the contribution of image regions affected by signal dropouts. Corresponding weight maps were estimated by a sliding-window algorithm, which analyzed signal deviations from a patch-wise reference. In order to ensure the computation of a robust reference, repetitions were filtered by a classifier that was trained to detect images corrupted by signal dropouts. The proposed method, named Deep Learning-guided Adaptive Weighted Averaging (DLAWA), was evaluated in terms of dropout suppression capability, bias reduction in the ADC, and noise characteristics. Results In the case of uniform averaging, motion-related dropouts caused signal attenuation and ADC overestimation in parts of the liver, with the left lobe being affected particularly. Both effects could be substantially mitigated by DLAWA while preventing global penalties with respect to SNR due to local signal suppression. Performing evaluations on patient data, the capability to recover lesions concealed by signal dropouts was demonstrated as well. Further, DLAWA allowed for transparent control of the trade-off between SNR and signal dropout suppression by means of a few hyperparameters. Conclusion This work presents an effective and flexible method for the local compensation of signal dropouts resulting from motion and pulsation. Because DLAWA follows a retrospective approach, no changes to the acquisition are required.
CRIS-Team WoS Importer:2022-08-12

Differences and Similarities in the Pattern of Early Metabolic and Morphologic Response after Induction Chemo-Immunotherapy versus Induction Chemotherapy Alone in Locally Advanced Squamous Cell Head and Neck Cancer - Beck, Michael; Semrau, Sabine; Haderlein, Marlen; Gostian, Antoniu-Oreste; Hartwich, Julius; Müller, Sarina Katrin; Kallies, Annett; Geppert, Carol-Immanuel; Schonath, Miriam; Putz, Florian; Gaipl, Udo; Frey, Benjamin; et al. (Cancers, 2022)
Simple Summary There are differences and similarities when assessing the short-term therapeutic response of chemotherapy and chemotherapy plus immunotherapy using imaging techniques, which may be necessary to make treatment decisions in malignant head and neck tumors. After both chemo- and immunochemotherapy, remission becomes measurable in cross-sectional and metabolic diagnostics after only one cycle of therapy, with (18)FDG-PET/CT predicting complete remission of tumor cells in a representative biopsy better than MRI/CT examination in both therapeutic modalities. While complete tumor remission is highly likely (88%) after immunochemotherapy in tumors with low residual activity (<= 40% of initial SUV), this is less common after chemotherapy alone (65%). In metabolic nonresponse with more than 80% residual activity, the probability of complete remission nevertheless is low after chemotherapy alone (6%). After immunochemotherapy, these false nonresponders are common (35%), requiring additional diagnostics by deep biopsy. Cases of pseudoprogression with an increase of SUVmax of more than 125% of the baseline were not observed. Background: In head and neck cancer patients, parameters of metabolic and morphologic response of the tumor to single-cycle induction chemotherapy (IC) with docetaxel, cis- or carboplatin are used to decide the further course of treatment. This study investigated the effect of adding a double immune checkpoint blockade (DICB) of tremelimumab and durvalumab to IC on imaging parameters and their significance with regard to tumor cell remission. Methods: Response variables of 53 patients treated with IC+DICB (ICIT) were compared with those of 104 who received IC alone. Three weeks after one cycle, pathologic and, in some cases, clinical and endoscopic primary tumor responses were evaluated and correlated with a change in 18F-FDG PET and CT/MRI-based maximum-standardized uptake values (SUVmax) before (SUV(max)pre), after treatment (SUV(max)post) and residually (resSUV(max) in % of SUV(max)pre), and in maximum tumor diameter (D-max) before (D(max)pre) and after treatment (D(max)post) and residually (resD). Results: Reduction of SUVmax and D-max occurred in both groups; values were SUV(max)pre: 14.4, SUV(max)post: 6.6, D(max)pre: 30 mm and D(max)post: 23 mm for ICIT versus SUV(max)pre: 16.5, SUV(max)post: 6.4, D(max)pre: 21 mm, and D(max)post: 16 mm for IC alone (all p < 0.05). ResSUV(max) was the best predictor of complete response (IC: AUC: 0.77; ICIT: AUC: 0.76). Metabolic responders with resSUV(max) <= 40% tended to have a higher rate of CR to ICIT (88%; n = 15/17) than to IC (65%; n = 30/46; p = 0.11). Of the metabolic nonresponders (resSUV(max) > 80%), 33% (n = 5/15) achieved a clinical CR to ICIT versus 6% (n = 1/15) to IC (p = 0.01). Conclusions: ICIT and IC quickly induce a response and 18F-FDG PET is the more accurate modality for identifying complete remission. The rate of discrepant response, i.e., pCR with metabolic nonresponse after ICIT was >30%.
CRIS-Team WoS Importer:2022-10-21

Discrimination between Inflammatory and Fibrotic Activity in Crohn's Disease-Associated Ileal-Colonic Anastomotic Strictures by Combined Ga-68-FAPI-46 and F-18-FDG-PET/CT Imaging - Beck, Michael; Kuwert, Torsten; Atzinger, Armin; Gerner, Maximilian; Hartmann, Arndt; Saake, Marc; Uder, Michael; Neurath, Markus; Atreya, Raja (Visceral Medicine, 2024)
Introduction: The development of an intestinal stricture in patients with Crohn s disease represents an important and frequent complication, reflecting the progressive nature of the disease. Depending on the inflammatory and fibrotic composition of the stricture, intensified medical therapy, interventional endoscopy, or surgical intervention is required. However, currently available diagnostic approaches can only assess the level of inflammation, but not the degree of fibrosis, limiting rational therapeutic management of Crohn s disease patients. Recently, prolyl endopeptidase fibroblast activating protein (FAP) has been functionally implicated in fibrotic tissue remodelling, indicating it as a promising target for detection of sites of fibrotic tissue remodelling. Thus, intestinal fibrosis might be visualized using Gallium-68 labelled inhibitors of FAP (FAPI). While F-18-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/CT is a standard diagnostic tool for visualizing inflammatory processes, we combined Ga- 68-FAPI-46-PET/CT and F-18-FDG-PET/CT to differentiate predominantly fibrotic or inflammatory areas in Crohn s disease patients with ileo-colonic strictures. Methods: In our study, we analysed three Crohn s disease patients with anastomotic ileo-colonic strictures who underwent both dynamic Ga-68-FAPI-46-PET/CT and static F-18-FDG-PET/CT imaging to assess the level of visualized fibrotic areas within the stricture and differentiate it from inflammatory ones. PET images were analysed both visually and quantitatively. Furthermore, conventional MR enterography and endoscopy were performed in parallel to correlate observed findings. Two of the included patients underwent surgery and the histological specimen were analysed for the level of inflammation and fibrosis, which results were similarly compared to the findings of the PET imaging procedures. Results: Different uptake patterns of Ga-68- FAPI-46 could be observed in the anastomotic ileo-colonic strictures of the examined Crohn s disease patients, respectively. Immunohistochemical analyses demonstrated that there was a correlation between the level of Ga-68- FAPI-46 uptake and severity of fibrosis, while FDG uptake correlated with the inflammatory activity in the analysed strictures. Discussion: The combination with F-18-FDGPET/CT represents a promising imaging modality to distinguish inflammation from fibrosis and guide subsequent therapy in stricturing Crohn s disease patients, warranting further studies.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Crohn s disease; FAPI-PET/CT; Fibrosis; Ga-68-FAPI-46; Strictures

Dynamic CT angiography for therapy evaluation after transarterial chemoembolization of hepatocellular carcinoma - Saake, Marc; Seuß, Hannes; Hammon, Matthias; Ellmann, Stephan; May, Matthias; Uder, Michael; Schmid, Axel (Acta Radiologica, 2019)
Background: Liver dynamic computed tomography (CT) is an established method for pre- and post-interventional evaluation of hepatocellular carcinoma. To date only the liver parenchyma and perfusion information of dynamic CT has been evaluated widely. Purpose: To evaluate the vascular information contained in dynamic CT datasets. Material and Methods: Dynamic CT performed one day after transarterial chemoembolization (60 mL of contrast medium, 6 mL/s, 40 s scan duration) were retrospectively evaluated. Conventional slice and angiographic maximum-intensity-projection reconstructions were calculated on a multi-modality post-processing platform. Datasets were evaluated for viable tumor, anatomy of the vasculature, and potential tumor-feeding vessels. The results were compared to digital subtraction angiography images. Results: In total, 94 treated hepatocellular carcinoma nodules were evaluated (62 dynamic CT scans, 46 patients [34 men; mean age = 69 years]). Forty-six partially viable tumors were diagnosed after transarterial chemoembolization. In all of these, tumor-feeding vessels were found in dynamic CT. Seventeen suspected extra-hepatic tumor feeders were reported, of which 14 had not been found during previous transarterial chemoembolization. Conclusion: Dynamic CT is useful in post-interventional imaging of hepatocellular carcinoma after transarterial chemoembolization due to its ability to detect residual viable tumor parts and to show previously unknown intra- and extra-hepatic tumor-feeding vessels.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Abdomen; chemoembolization; computed tomography angiography; interventional; liver

Erratum to 'Clinical/perfusion CT CBV mismatch as prognostic factor in intraarterial thrombectomy in acute anterior circulation stroke' (Clinical Neurology and Neurosurgery (2014) 121, (39-45)) - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd; Kloska, Stephan (Clinical Neurology and Neurosurgery, 2014)
CRIS-Team Scopus Importer:2022-08-05

Extent of simultaneous radiation dose and iodine reduction at stable image quality in computed tomography of the chest: A systematic approach using automated tube voltage adaption and iterative reconstructions - Eller, Achim; Wüst, Wolfgang; Saake, Marc; Ellmann, Stephan; Kämmerer, Nadine; Hammon, Matthias; Janka, Rolf Matthias; Uder, Michael; May, Matthias (Medicine, 2018)
BACKGROUND: Aim of this study was to systematically combine tube voltage adaptation and iterative reconstructions for reduction of iodine and radiation dose. METHODS: Settings for the study protocol were evaluated in ex-ante trials to provide image quality that is comparable to a reference protocol at 120 kV with tube current modulation. Consecutive patients were randomized to undergo computed tomography (CT) of the chest using the study protocol (n = 62) or reference protocol (n = 50). Objective and subjective image quality was assessed and compared. RESULTS: Tube voltage was decreased to 100 kV in 47 patients and to 80 kV in 15 patients in the study group. The iodine dosage (16.1 vs 10.5 g) and the effective radiation dose (3.6 vs 2.5 mSv) were significantly decreased in the study group (both P < .001). Contrast-to-noise ratio was comparable in the pulmonary trunk and increased in the aorta (P < .01). Subjective image quality was comparable without statistically significance. CONCLUSIONS: Simultaneous reductions in iodine dosage and radiation dose by one-third are feasible for CT of the chest.
EVALuna2:34701

Feature-guided deep learning reduces signal loss and increases lesion CNR in diffusion-weighted imaging of the liver - Führes, Tobit; Saake, Marc; Lorenz, Jennifer; Seuß, Hannes; Bickelhaupt, Sebastian; Uder, Michael; Laun, Frederik Bernd (Zeitschrift für Medizinische Physik, 2023)
Purpose: This research aims to develop a feature-guided deep learning approach and compare it with an optimized conventional post-processing algorithm in order to enhance the image quality of diffusion-weighted liver images and, in particular, to reduce the pulsation-induced signal loss occurring predominantly in the left liver lobe. Methods: Data from 40 patients with liver lesions were used. For the conventional approach, the best-suited out of five examined algorithms was chosen. For the deep learning approach, a U-Net was trained. Instead of learning “gold-standard” target images, the network was trained to optimize four image features (lesion CNR, vessel darkness, data consistency, and pulsation artifact reduction), which could be assessed quantitatively using manually drawn ROIs. A quality score was calculated from these four features. As an additional quality assessment, three radiologists rated different features of the resulting images. Results: The conventional approach could substantially increase the lesion CNR and reduce the pulsation-induced signal loss. However, the vessel darkness was reduced. The deep learning approach increased the lesion CNR and reduced the signal loss to a slightly lower extent, but it could additionally increase the vessel darkness. According to the image quality score, the quality of the deep-learning images was higher than that of the images obtained using the conventional approach. The radiologist ratings were mostly consistent with the quantitative scores, but the overall quality ratings differed among the readers. Conclusion: Unlike the conventional algorithm, the deep-learning algorithm increased the vessel darkness. Therefore, it may be a viable alternative to conventional algorithms.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Cardiac motion artifact; Deep learning; Diffusion; Liver; Neural network; Oncology

Flat detector computed tomography angiography with intravenous contrast application: Feasibility for visualization of cerebral arterial vasculature - Saake, Marc; Breuer, Lorenz; Gölitz, Philipp; Ott, Sabine; Struffert, Tobias; Dörfler, Arnd (Journal of Neuroimaging, 2013)
BACKGROUND AND PURPOSE: The aim of our study was to evaluate flat detector computed tomography angiography with peripheral intravenous contrast material application (FD-CTA) for visualization of cerebral arteries in comparison with intravenous multidetector computed tomography angiography (CTA) and intraarterial digital subtraction angiography (DSA). METHODS: The study was approved by the local institutional review board and informed consent was obtained by all participants. Ten patients underwent FD-CTA, CTA, and DSA of the cerebral arterial vasculature for suspected cerebrovascular disease. The image data were evaluated by two readers in consensus for the visualization of cerebral arterial segments on a 5-point scale (0 = vessel cannot be distinguished; 4 = excellent image quality). The Wilcoxon signed-rank test was used for statistical analysis. Note that P < .05 was considered to indicate a significant difference. RESULTS: The depiction of cerebral arterial segments with FD-CTA was significantly superior compared to CTA in most vessel segments (P < .05 in 20 of 23 anatomic regions) and was without significant difference compared with DSA in large and medium intracranial vessels. CONCLUSIONS: The results suggest that the cerebral arteries can be visualized by FD-CTA in high resolution, in many vessel segments comparable to DSA. © 2012 by the American Society of Neuroimaging.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiography; Cerebral; Computed tomography; Flat detector; Intravenous

Flow-compensated diffusion encoding in MRI for improved liver metastasis detection - Laun, Frederik Bernd; Führes, Tobit; Seuß, Hannes; Müller, Astrid; Bickelhaupt, Sebastian; Stemmer, Alto; Benkert, Thomas; Uder, Michael; Saake, Marc (PLoS ONE, 2022)
Magnetic resonance (MR) diffusion-weighted imaging (DWI) is often used to detect focal liver lesions (FLLs), though DWI image quality can be limited in the left liver lobe owing to the pulsatile motion of the nearby heart. Flow-compensated (FloCo) diffusion encoding has been shown to reduce this pulsation artifact. The purpose of this prospective study was to intra-individually compare DWI of the liver acquired with conventional monopolar and FloCo diffusion encoding for assessing metastatic FLLs in non-cirrhotic patients. Forty patients with known or suspected multiple metastatic FLLs were included and measured at 1.5 T field strength with a conventional (monopolar) and a FloCo diffusion encoding EPI sequence (single refocused; b-values, 50 and 800 s/mm2). Two board-certified radiologists analyzed the DWI images independently. They issued Likert-scale ratings (1 = worst, 5 = best) for pulsation artifact severity and counted the difference of lesions visible at b = 800 s/mm2 separately for small and large FLLs (i.e., < 1 cm or > 1 cm) and separately for left and right liver lobe. Differences between the two diffusion encodings were assessed with the Wilcoxon signed-rank test. Both readers found a reduction in pulsation artifact in the liver with FloCo encoding (p < 0.001 for both liver lobes). More small lesions were detected with FloCo diffusion encoding in both liver lobes (left lobe: six and seven additional lesions by readers 1 and 2, respectively; right lobe: five and seven additional lesions for readers 1 and 2, respectively). Both readers found one additional large lesion in the left liver lobe. Thus, flow-compensated diffusion encoding appears more effective than monopolar diffusion encoding for the detection of liver metastases.
CRIS-Team Scopus Importer:2022-08-05

Full field digital mammography (FFDM) versus cmos technology, specimen radiography system (SRS) and tomosynthesis (DBT) - Which system can optimise surgical therapy? - Schulz-Wendtland, Rüdiger; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Brehm, Barbara; Hammon, Matthias; Saake, Marc; Dankerl, Peter; Jud, Sebastian; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: This prospective clinical study aimed to evaluate whether it would be possible to reduce the rate of re-excisions using CMOS technology, a specimen radiography system (SRS) or digital breast tomosynthesis (DBT) compared to a conventional full field digital mammography (FFDM) system. Material and Method: Between 12/2012 and 2/2013 50 patients were diagnosed with invasive breast cancer (BI-RADS™ 5). After histological verification, all patients underwent breast-conserving therapy with intraoperative imaging using 4 different systems and differing magnifications: 1. Inspiration™ (Siemens, Erlangen, Germany), amorphous selenium, tungsten source, focus 0.1 mm, resolution 85 m pixel pitch, 8 lp/mm; 2. BioVision™ (Bioptics, Tucson, AZ, USA), CMOS technology, photodiode array, flat panel, tungsten source, focus 0.05, resolution 50 m pixel pitch, 12 lp/mm; 3. the Trident™ specimen radiography system (SRS) (Hologic, Bedford, MA, USA), amorphous selenium, tungsten source, focus 0.05, resolution 70 m pixel pitch, 7.1 lp/mm; 4. tomosynthesis (Siemens, Erlangen, Germany), amorphous selenium, tungsten source, focus 0.1 mm, resolution 85 m pixel pitch, 8 lp/mm, angular range 50 degrees, 25 projections, scan time > 20 s, geometry: uniform scanning, reconstruction: filtered back projection. The 600 radiographs were prospectively shown to 3 radiologists. Results: Of the 50 patients with histologically proven breast cancer (BI-RADS™ 6), 39 patients required no further surgical therapy (re-excision) after breast-conserving surgery. A retrospective analysis (n = 11) showed a significant (p < 0.05) increase of sensitivity with the BioVision™, the Trident™ and tomosynthesis compared to the Inspiration™ at a magnification of 1.0: 2.0 or 1.0: 1.0 (tomosynthesis) (2.6, 3.3 or 3.6 %), i.e. re-excision would not have been necessary in 2, 3 or 4 patients, respectively, compared to findings obtained with a standard magnification of 1.0: 1.0. Conclusion: The sensitivity of the BioVision™, the Trident™ and tomosynthesis was significantly (p < 0.05) higher and the rate of re-excisions was reduced compared to FFDM using a conventional detector at a magnification of 2.0 but without zooming. © Georg Thieme Verlag KG Stuttgart New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast; breast cancer; breast malignancy; mammography

Functional Brain Imaging Reveals Rapid Blockade of Abdominal Pain Response Upon Anti-TNF Therapy in Crohn's Disease - Heß, Andreas; Roesch, Julie; Saake, Marc; Sergeeva, Marina; Hirschmann, Simon; Neumann, Helmut; Dörfler, Arnd; Neurath, Markus; Atreya, Raja (Gastroenterology, 2015)
EVALuna2:2003

Gadolinium-based contrast agents: What we learned from acute adverse events, nephrogenic systemic fibrosis and brain retention - Bäuerle, Tobias; Saake, Marc; Uder, Michael (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Radiologists have been administering gadolinium-based contrast agents (GBCA) in magnetic resonance imaging for several decades, so that there is abundant experience with these agents regarding allergic-like reactions, nephrogenic systemic fibrosis (NSF) and gadolinium retention in the brain.
CRIS-Team WoS Importer:2021-01-22

High resolution time-of-flight MR-angiography at 7 T exploiting VERSE saturation, compressed sensing and segmentation - Meixner, Christian; Liebig, Patrick; Speier, Peter; Forman, Christoph; Hensel, Bernhard; Schmidt, Manuel; Saake, Marc; Uder, Michael; Dörfler, Arnd; Heidemann, Robin M.; Schmitter, Sebastian; Nagel, Armin Michael (Magnetic Resonance Imaging, 2019)
Background: 3D Time-of-Flight (TOF) MR-angiography (MRA) substantially benefits from ultra-high magnetic field strengths (≥7 T) due to increased Signal-to-Noise ratio and improved contrast. However, high-resolution TOF-MRA usually requires long acquisition times. In addition, specific absorption rate constraints limit the choice of optimal pulse sequence parameters, especially if venous saturation is employed. Purpose: To implement and evaluate an arterial TOF-MRA for accelerated high-resolution angiography at ultra-high magnetic field strength. Field strengths/sequence: 7 T modified gradient-echo TOF sequence including venous saturation using Variable-Rate Selective Excitation (VERSE), Compressed Sensing (CS) and sparse application of saturation pulses, called segmentation, were included for acceleration. Assessment: To analyze the acceleration techniques all volunteers were examined with the same protocols. CS with different sampling patterns and regularization factors as well as segmentation were applied for acceleration. For comparison, conventional acceleration techniques were applied (GRAPPA PAT 3 and Partial Fourier (6/8 in slice/phase encoding)). Images were co-registered and 40 mm thick transversal maximum intensity projections were created to calculate the relative number of vessels. To analyze the visibility of small vessels, the lenticulostriate arteries (LSA) were examined. This was done via multiscale vessel enhancement filtering in a VOI and quantification via Fiji ImageJ as well as qualitatively evaluation by two radiologists. Additionally, the venous/arterial vessel-to-background ratios (vVBR/aVBR) were calculated for chosen protocols. Results: For the acceleration of a high resolution TOF-MRA (0.31 mm isotropic), under-sampling of 9.6 showed aliasing artifacts, whereas 7.2 showed no aliasing. The regularization factor R had a strong impact on the image quality according to smoothing (R = 0.01 to R = 0.005) and noise (R = 0.0005 to R = 0.00005). With the alternating sampling patterns it was shown that the k-space center should not be under-sampled too much. Additionally segmentation could be verified to be feasible for stronger acceleration with sufficient venous suppression. Conclusion: The combination of several independent techniques (VERSE, CS with acceleration factor 7.2, R = 0.001, Poisson disc radius of 80%, 3 segments) enables the application of high-resolution (0.31 mm isotropic) TOF-MRA with venous saturation at 7 T in clinical time settings (TA ≈ 5 min) and within the SAR limits.
CRIS-Team Scopus Importer:2019-08-30
Keywords: 7 Tesla; Compressed sensing; MR-angiography; Time-of-flight; Ultra-high field; VERSE

Image Quality and Detection of Small Focal Liver Lesions in Diffusion-Weighted Imaging Comparison of Navigator Tracking and Free-Breathing Acquisition - Saake, Marc; Seuß, Hannes; Riexinger, Andreas; Bickelhaupt, Sebastian; Hammon, Matthias; Uder, Michael; Laun, Frederik Bernd (Investigative Radiology, 2021)
Objectives The aim of this study was to compare intraindividual diffusion-weighted imaging (DWI) of the liver acquired with free breathing (FB) versus navigator triggering (NT) for assessing small focal liver lesions (FLLs) in noncirrhotic patients. Materials and Methods Patients with known or suspected multiple FLLs were prospectively included, and spin-echo echo-planar DWI with NT and FB acquisition was performed (b-values, 50 and 800 s/mm(2) [b50 and b800]). NT and FB DWI sequences with similar acquisitions times were used. Liver and lesion signal-to-noise ratios were measured at b800. The DWI scans were analyzed independently by 2 readers. Liver edge delineation, presence of stair-step artifacts, vessel sharpness, severity of cardiac motion artifacts, overall image quality, and lesion conspicuity were rated with 5-point Likert scales. Small and large FLLs (ie, <1 cm or >= 1 cm) were rated separately for lesion conspicuity. The FLL detectability was estimated by comparing the number of lesions visible with FB to those visible with NT. Results Forty-three patients were included in the study. The FB acquisition performed better in terms of severity of cardiac motion artifacts. The NT performed better in terms of liver edge delineation and vessel sharpness. Little difference was found for stair-step artifact, overall image quality, and conspicuity of large FLL, whereas the conspicuity of small FLL was better for NT. For small FLL, both readers found more lesions with NT in 11 cases at b800. For large FLL, this effect was much less pronounced (1 case at b800 reported by 1 of the readers). The mean liver and lesion signal-to-noise ratios were 16.8/41.5 and 19.8/38.4 for NT/FB, respectively. Conclusions Small FLL detection is better with NT. Large FLL detection by FB and NT is similarly good. We conclude that NT should be used.
CRIS-Team WoS Importer:2021-09-03

Imaging Hepatocellular Carcinoma with Dynamic CT Before and After Transarterial Chemoembolization: Optimal Scan Timing of Arterial Phase - Saake, Marc; Lell, Michael; Eller, Achim; Wüst, Wolfgang; Heinz, Marco; Uder, Michael; Schmid, Axel (Academic Radiology, 2015)
The aim of this study was to determine the optimal arterial phase delay for computed tomography imaging of hepatocellular carcinoma (HCC) before and after transarterial chemoembolization (TACE) using a low iodine dose protocol.A total of 39 patients with known HCC were imaged with dynamic computed tomography of the liver (40-second scan duration, 60 mL of contrast medium), both on the same day before TACE and 1 day after TACE. Time attenuation curves of vessels, nonmalignant liver parenchyma, and 62 HCCs were normalized to a uniform aortic contrast arrival and analyzed.Maximal arterial phase HCC to liver contrast was reached between 13 and 17 seconds after aortic contrast arrival, both before and after TACE.Using our low iodine dose protocol, arterial phase imaging of HCC should be performed between 13 and 17 seconds after aortic contrast arrival, both before and after TACE.
EVALuna2:14493

Impact of velocity- and acceleration-compensated encodings on signal dropout and black-blood state in diffusion-weighted magnetic resonance liver imaging at clinical TEs - Führes, Tobit; Saake, Marc; Szczepankiewicz, Filip; Bickelhaupt, Sebastian; Uder, Michael; Laun, Frederik Bernd (PLoS ONE, 2023)
Purpose The study aims to develop easy-to-implement concomitant field-compensated gradient waveforms with varying velocity-weighting (M1) and acceleration-weighting (M2) levels and to evaluate their efficacy in correcting signal dropouts and preserving the black-blood state in liver diffusion-weighted imaging. Additionally, we seek to determine an optimal degree of compensation that minimizes signal dropouts while maintaining blood signal suppression. Methods Numerically optimized gradient waveforms were adapted using a novel method that allows for the simultaneous tuning of M1- and M2-weighting by changing only one timing variable. Seven healthy volunteers underwent diffusion-weighted magnetic resonance imaging (DWI) with five diffusion encoding schemes (monopolar, velocity-compensated (M1 = 0), acceleration-compensated (M1 = M2 = 0), 84%-M1–M2-compensated, 67%-M1–M2-compensated) at b-values of 50 and 800 s/mm2 at a constant echo time of 70 ms. Signal dropout correction and apparent diffusion coefficients (ADCs) were quantified using regions of interest in the left and right liver lobe. The blood appearance was evaluated using two five-point Likert scales. Results Signal dropout was more pronounced in the left lobe (19%-42% less signal than in the right lobe with monopolar scheme) and best corrected by acceleration-compensation (8%-10% less signal than in the right lobe). The black-blood state was best with monopolar encodings and decreased significantly (p < 0.001) with velocity- and/or acceleration-compensation. The partially M1–M2-compensated encoding schemes could restore the black-blood state again. Strongest ADC bias occurred for monopolar encodings (difference between left/right lobe of 0.41 μm2/ms for monopolar vs. < 0.12 μm2/ms for the other encodings). Conclusion All of the diffusion encodings used in this study demonstrated suitability for routine DWI application. The results indicate that a perfect value for the level of M1–M2-compensation does not exist. However, among the examined encodings, the 84%-M1–M2-compensated encodings provided a suitable tradeoff.
CRIS-Team Scopus Importer:2023-10-20

Improved Visualization of Prostate Cancer Using Multichannel Computed Diffusion Images: Combining ADC and DWI - Hammon, Matthias; Saake, Marc; Laun, Frederik Bernd; Heiß, Rafael; Seuss, Nicola; Janka, Rolf Matthias; Cavallaro, Alexander Josef; Uder, Michael; Seuß, Hannes (Diagnostics, 2022)
(1) Background: For the peripheral zone of the prostate, diffusion weighted imaging (DWI) is the most important MRI technique; however, a high b-value image (hbDWI) must always be evaluated in conjunction with an apparent diffusion coefficient (ADC) map. We aimed to unify the important contrast features of both a hbDWI and ADC in one single image, termed multichannel computed diffusion images (mcDI), and evaluate the values of these images in a retrospective clinical study; (2) Methods: Based on the 2D histograms of hbDWI and ADC images of 70 patients with histologically proven prostate cancer (PCa) in the peripheral zone, an algorithm was designed to generate the mcDI. Then, three radiologists evaluated the data of 56 other patients twice in three settings (T2w images +): (1) hbDWI and ADC; (2) mcDI; and (3) mcDI, hbDWI, and ADC. The sensitivity, specificity, and inter-reader variability were evaluated; (3) Results: The overall sensitivity/specificity were 0.91/0.78 (hbDWI + ADC), 0.85/0.88 (mcDI), and 0.97/0.88 (mcDI + hbDWI + ADC). The kappa-values for the inter-reader variability were 0.732 (hbDWI + ADC), 0.800 (mcDI), and 0.853 (mcDI + hbDWI + ADC). (4) Conclusions: By using mcDI, the specificity of the MRI detection of PCa was increased at the expense of the sensitivity. By combining the conventional diffusion data with the mcDI data, both the sensitivity and specificity were improved.
CRIS-Team WoS Importer:2022-08-12

Influence of Artifact Corrections on MRI Signal Intensity Ratios for Assessment of Gadolinium Brain Retention - Saake, Marc; Hepp, Tobias; Schmidle, Alexandra; Wüst, Wolfgang; Heiß, Rafael; Dörfler, Arnd; Uder, Michael; Bäuerle, Tobias (Academic Radiology, 2019)
Rationale and Objectives: Differences in brain signal intensity ratios (SIRs) of deep brain nuclei in T1-weighted (T1w) magnetic resonance images were reported as an indicator of gadolinium brain retention. Variable methods of image reconstruction and inhomogeneity correction for T1w images exist, which might affect the accuracy of SIRs. The aim of our prospective study was to investigate the effect of flow artifact compensation (FAC) and intensity inhomogeneity correction (IIC) on the dentate nucleus-to-pons and globus pallidus-to-thalamus SIRs in study participants who had previously received multiple doses of gadobutrol. Materials and Methods: This study included 76 participants who received five or more gadobutrol-enhanced scans between 2007 and 2017. A control group of 25 participants without gadolinium-based contrast agent application in their patient history was included for comparison. Unenhanced brain magnetic resonance imaging including two T1w spin-echo sequences with and without FAC was performed in all participants. Both sequences were reconstructed with and without IIC. Images were assessed for flow artifacts and SIRs were calculated. Results: Using FAC, a lower proportion of participants had to be excluded from the final analysis of dentate nucleus-to-pons SIR due to flow artifacts (15% versus 46%, p < 0.001). Without IIC, a difference was found between the study and the control group for the dentate nucleus-to-pons ratio (p = 0.004), but not for the same sequence reconstructed with IIC (p = 0.29). For the globus pallidus-to-thalamus ratio, no difference was found between the study and control group. Conclusion: The application of an IIC algorithm has significant impact on brain nuclei SIRs for the assessment of gadolinium brain retention.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Contrast Media; Gadolinium; Magnetic resonance imaging

Influence of different reconstruction parameters in the visualization of intracranial stents using C-arm flat panel CT angiography: experience in an animal model - Ott, Sabine; Struffert, Tobias; Saake, Marc; Gölitz, Philipp; Adamek, Edyta; Dörfler, Arnd (Acta Radiologica, 2016)
C-arm flat panel computed tomography angiography (CA-CTA) is a relatively new imaging modality. Consequently, knowledge about postprocessing parameters and their influence on image quality is still limited, especially for the visualization of implanted microstents.To optimize reconstruction parameters by evaluating the influence of these different parameters for CA-CTA visualization of microstents in an animal model.Eleven microstents were implanted within the left common carotid artery of 11 New Zealand white rabbits. Both CA-CTA, using intra-venous delivery of contrast material, and conventional digital subtraction angiography (DSA) was performed. CA-CTA datasets were reconstructed using three different image characteristics (normal, sharp, smooth). Two experienced neuroradiologists evaluated the image quality and performed measurements of inner and outer stent diameters as well as measurements of the lumen area.Stent deployment was performed successfully in all animals. Inter-observer correlation coefficient for all measurements was high (r = 0.87-0.92). Lumen area and inner stent diameter were significantly smaller in image characteristic "smooth" (P < 0.01) than in "sharp" and "normal". Outer stent diameter was larger in "smooth" than in "sharp" and "normal" (P < 0.01). Stent strut size was significantly wider using image characteristic "smooth". "Sharp" and "normal" compared best to DSA, with "sharp" providing the closest match to DSA measurements, with the trade-off of significantly more noise than in the "normal" reconstructions.The use of different image characteristics in the postprocessing of CA-CTA datasets has an influence on the visualization of implanted stents. Image characteristic "sharp" and "normal" compared best to DSA.
EVALuna2:14583

Influence of saturation effects on biexponential liver intravoxel incoherent motion - Loh, Martin; Führes, Tobit; Stuprich, Christoph; Uder, Michael; Saake, Marc; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2023)
Purpose: Studies on intravoxel incoherent motion (IVIM) imaging in the liver have been carried out with different acquisition protocols. The number of acquired slices and the distances between slices can influence IVIM measurements due to saturation effects, but these effects have often been disregarded. This study investigated differences in biexponential IVIM parameters between two slice settings. Methods: Fifteen healthy volunteers (21–30 years) were examined at a field strength of 3 T. Diffusion-weighted images of the abdomen were acquired with 16 b values (0–800 s/mm2), with four slices for the few slices setting and 24–27 slices for the many slices setting. Regions of interest were manually drawn in the liver. The data were fitted with a monoexponential signal curve and a biexponential IVIM curve, and biexponential IVIM parameters were determined. The dependence on the slice setting was assessed with Student's t test for paired samples (normally distributed IVIM parameters) and the Wilcoxon signed-rank test (non-normally distributed parameters). Results: None of the parameters were significantly different between the settings. For few slices and many slices, respectively, the mean values (SDs) for (Formula presented.) were (Formula presented.) ((Formula presented.)) and (Formula presented.) ((Formula presented.)); for (Formula presented.) they were 29.7% (6.2%) and 27.7% (3.6%); and for (Formula presented.) they were (Formula presented.) ((Formula presented.)) and (Formula presented.) ((Formula presented.)). Conclusion: Biexponential IVIM parameters in the liver are comparable among IVIM studies that use different slice settings, with mostly negligible saturation effects. However, this may not hold for studies that use much shorter TR.
CRIS-Team Scopus Importer:2023-03-24
Keywords: diffusion; IVIM; liver; perfusion; saturation effects

Intraprocedural angiographic CT as a valuable tool in the course of endovascular treatment of direct sinus cavernous fistulas - Gölitz, Philipp; Struffert, Tobias; Saake, Marc; Knossalla, F.; Dörfler, Arnd (Interventional Neuroradiology, 2012)
This investigation aimed to demonstrate the potential of intraprocedural angiographic CT in monitoring complex endovascular coil embolization of direct carotid cavernous fistulas. Angiographic CT was performed as a dual rotational 5 s run with intraarterial contrast medium injection in two patients during endovascular coil embolization of direct carotid cavernous fistulas. Intraprocedural angiographic CT was considered helpful if conventional 2D series were not conclusive concerning coil position or if a precise delineation of the parent artery was impossible due to a complex anatomy or overlying coil material. During postprocessing multi-planar reformatted and dual volume images of angiographic CT were reconstructed. Angiographic CT turned out to be superior in the intraprocedural visualization of accidental coil migration into the parent artery where conventional 2D-DSA series failed to reliably detect coil protrusion. The delineation of coil protrusion by angiographic CT allowed immediate correct coil repositioning to prevent parent artery compromising. Angiographic CT can function as a valuable intraprocedurally feasible tool during complex coil embolizations of direct carotid cavernous fistulas. It allows the precise visualization of the cerebral vasculature and any accidental coil protrusion can be determined accurately in cases where conventional 2D-DSA series are unclear or compromised. Thus angiographic CT might contribute substantially to reduce procedural complications and to increase safety in the management of endovascular treatment of direct carotid cavernous fistulas.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Carotid cavernous fistula; Endovascular approach; Intraprocedural angiographic CT; Transarterial coil embolization

Local control of perivascular malignant liver lesions using percutaneous irreversible electroporation: initial experiences - Eller, Achim; Schmid, Andrea; Schmidt, Joachim; May, Matthias; Brand, Michael; Saake, Marc; Uder, Michael; Lell, Michael (Cardiovascular and Interventional Radiology, 2015)
This study was designed to assess efficacy and safety in the treatment of perivascular malignant liver lesions using percutaneous, computed tomography (CT)-guided irreversible electroporation (IRE).Fourteen patients (mean age 58 ± 11 years) with 18 malignant liver lesions were consecutively enrolled in this study. IRE was performed in patients not eligible for surgery and lesions abutting large vessels or bile ducts. Follow-up exams were performed using multislice-CT (MS-CT) or MRI.Medium lesion diameter was 20 ± 5 mm. Ten of 14 (71 %) were successfully treated with no local recurrence to date (mean follow-up 388 ± 160 days). One case left initial tumor control unclear and additional RFA was performed 4 weeks after IRE. Complications occurred in 4 of 14 (29 %) cases. In one case, intervention was terminated and abdominal bleeding required laparotomy. In two cases, a postinterventional hematothorax required intervention. In another case, abdominal bleeding could be managed conservatively. No complications related to the bile ducts occurred.Percutaneous IRE seems to be effective in perivascular lesions but is associated with a higher complication rate compared with thermoablative techniques.
EVALuna2:14379

MRI Brain Signal Intensity and Relaxation Times in Individuals with Prior Exposure to Gadobutrol - Saake, Marc; Schmidle, Alexandra; Kopp, Markus; Hanspach, Jannis; Hepp, Tobias; Nagel, Armin Michael; Dörfler, Arnd; Uder, Michael; Bäuerle, Tobias; Laun, Frederik Bernd (Radiology, 2019)
Purpose: To perform follow-up brain MRI in volunteer participants who had previously received multiple doses of gadobutrol and to assess for changes in signal intensities and relaxation times.
CRIS-Team WoS Importer:2019-03-06

Multi-Dimensional Flow-Preserving Compressed Sensing (MuFloCoS) for Time-Resolved Velocity-Encoded Phase Contrast MRI - Hutter, Jana; Schmitt, Peter; Saake, Marc; Stübinger, Axel; Grimm, Robert; Forman, Christoph; Greiser, Andreas; Hornegger, Joachim; Maier, Andreas (IEEE Transactions on Medical Imaging, 2015)
4-D time-resolved velocity-encoded phase-contrast MRI (4-D PCI) is a fully non-invasive technique to assess hemodynamics in vivo with a broad range of potential applications in multiple cardiovascular diseases. It is capable of providing quantitative flow values and anatomical information simultaneously. The long acquisition time, however, still inhibits its wider clinical use. Acceleration is achieved at present using parallel MRI (pMRI) techniques which can lead to substantial loss of image quality for higher acceleration factors. Both the high-dimensionality and the significant degree of spatio-temporal correlation in 4-D PCI render it ideally suited for recently proposed compressed sensing (CS) techniques. We propose the Multi-Dimensional Flow-preserving Compressed Sensing (MuFloCoS) method to exploit these properties. A multi-dimensional iterative reconstruction is combined with an interleaved sampling pattern (I-VT), an adaptive masked and weighted temporal regularization (TMW) and fully automatically obtained vessel-masks. The performance of the novel method was analyzed concerning image quality, feasibility of acceleration factors up to 15, quantitative flow values and diagnostic accuracy in phantom experiments and an in vivo carotid study with 18 volunteers. Comparison with iterative state-of-the-art methods revealed significant improvements using the new method, the temporal normalized root mean square error of the peak velocity was reduced by 45.32% for the novel MuFloCoS method with acceleration factor 9. The method was furthermore applied to two patient cases with diagnosed high-grade stenosis of the ICA, which confirmed the performance of MuFloCoS to produce valuable results in the presence of pathological findings in 56 s instead of over 8 min (full sampling).
UnivIS-Import:2015-07-08:Pub.2015.tech.IMMD.IMMD5.multid
Keywords: Compressed sensing; hemodynamics; magnetic resonance imaging (MRI); phase contrast MRI

Non-Invasive Characterization of Experimental Bone Metastasis in Obesity Using Multiparametric MRI and PET/CT - Gregoric, Gasper; Gaculenko, Anastasia; Nagel, Lisa; Popp, Vanessa; Maschauer, Simone; Prante, Olaf; Saake, Marc; Schett, Georg; Uder, Michael; Ellmann, Stephan; Bozec, Aline; Bäuerle, Tobias (Cancers, 2022)
The growth of primary tumors and metastases is associated with excess body fat. In bone metastasis formation, the bone marrow microenvironment, and particularly adipocytes, play a pivotal role as growth mediators of disseminated tumor cells in the bone marrow. The aim of the present study is to non-invasively characterize the pathophysiologic processes in experimental bone metastasis resulting from accelerated tumor progression within adipocyte-rich bone marrow using multimodal imaging from magnetic resonance imaging (MRI) and positron emission tomography/computed tomography (PET/CT). To achieve this, we have employed small animal models after the administration of MDA-MB 231 breast cancer and B16F10 melanoma cells into the bone of nude rats or C57BL/6 mice, respectively. After tumor cell inoculation, ultra-high field MRI and mu PET/CT were used to assess functional and metabolic parameters in the bone marrow of control animals (normal diet, ND), following a high-fat diet (HFD), and/or treated with the peroxisome proliferator-activated receptor-gamma (PPAR gamma) antagonist bisphenol-A-diglycidylether (BADGE), respectively. In the bone marrow of nude rats, dynamic contrast-enhanced MRI (DCE-MRI) and diffusion-weighted imaging (DWI), as well as [F-18]fluorodeoxyglucose-PET/CT([F-18]FDG-PET/CT), was performed 10, 20, and 30 days after tumor cell inoculation, followed by immunohistochemistry. DCE-MRI parameters associated with blood volume, such as area under the curve (AUC), were significantly increased in bone metastases in the HFD group 30 days after tumor cell inoculation as compared to controls (p < 0.05), while the DWI parameter apparent diffusion coefficient (ADC) was not significantly different between the groups. [F-18]FDG-PET/CT showed an enhanced glucose metabolism due to increased standardized uptake value (SUV) at day 30 after tumor cell inoculation in animals that received HFD (p < 0.05). BADGE treatment resulted in the inversion of quantitative DCE-MRI and [F-18]FDG-PET/CT data, namely a significant decrease in AUC and SUV in HFD-fed animals as compared to ND-fed controls (p < 0.05). Finally, immunohistochemistry and qPCR confirmed the HFD-induced stimulation in vascularization and glucose activity in murine bone metastases. In conclusion, multimodal and multiparametric MRI and [F-18]FDG-PET/CT were able to derive quantitative parameters in bone metastases, revealing an increase in vascularization and glucose metabolism following HFD. Thus, non-invasive imaging may serve as a biomarker for assessing the pathophysiology of bone metastasis in obesity, opening novel options for therapy and treatment monitoring by MRI and [F-18]FDG-PET/CT.
CRIS-Team WoS Importer:2022-06-10

On the dependence of the cardiac motion artifact on the breathing cycle in liver diffusion-weighted imaging - Riexinger, Andreas; Laun, Frederik Bernd; Bickelhaupt, Sebastian; Seuß, Hannes; Uder, Michael; Hensel, Bernhard; Saake, Marc (PLoS ONE, 2020)
Purpose The purpose of this study was to investigate whether the cardiac motion artifact that regularly appears in diffusion-weighted imaging of the left liver lobe might be reduced by acquiring images in inspiration, when the coupling between heart and liver might be minimal. Materials and methods 43 patients with known or suspected focal liver lesions were examined at 1.5 T with breath hold acquisition, once in inspiration and once in expiration. Data were acquired with a diffusion-weighted echo planar imaging sequence and two b-values (b50 = 50 s/mm2 and b800 = 800 s/mm2). The severity of the cardiac motion artifact in the left liver lobe was rated by two experienced radiologists for both b-values with a 5 point Likert scale. Additionally, the normalized signal S(b800)/S(b50) in the left liver lobe was computed. The Wilcoxon signed-rank test was used comparing the scores of the two readers obtained in inspiration and expiration, and to compare the normalized signal in inspiration and expiration. Results The normalized signal in inspiration was slightly higher than in expiration (0.349±0.077 vs 0.336±0.058), which would indicate a slight reduction of the cardiac motion artifact, but this difference was not significant (p = 0.24). In the qualitative evaluation, the readers did not observe a significant difference for b50 (reader 1: p = 0.61; reader 2: p = 0.18). For b800, reader 1 observed a significant difference of small effect size favouring expiration (p = 0.03 with a difference of mean Likert scores of 0.27), while reader 2 observed no significant difference (p = 0.62). Conclusion Acquiring the data in inspiration does not lead to a markedly reduced cardiac motion artifact in diffusion-weighted imaging of the left liver lobe and is in this regard not to be preferred over acquiring the data in expiration.
CRIS-Team Scopus Importer:2020-10-16

Optimized angiographic computed tomography with intravenous contrast injection: An alternative to conventional angiography in the follow-up of clipped aneurysms? Clinical article - Gölitz, Philipp; Struffert, Tobias; Ganslandt, Oliver; Saake, Marc; Lücking, Hannes; Rösch, Julie; Knossalla, Frauke; Dörfler, Arnd (Journal of Neurosurgery, 2012)
Object. The purpose of this study was to evaluate the diagnostic accuracy of an optimized angiographic CT (ACT) program with intravenous contrast agent injection (ivACT) in the assessment of potential aneurysm remnants after neurosurgical clipping compared with conventional digital subtraction angiography (DSA). Methods. The authors report on 14 patients with 19 surgically clipped cerebral aneurysms who were scheduled to undergo angiographic follow-up. For each patient, the authors performed ivACT with dual rotational acquisition and conventional angiography including a 3D rotational run. The ivACT and 3D DSA data were reconstructed with different imaging modes, including a newly implemented subtraction mode with motion correction. Thereafter, the data sets were merged by the dual-volume technique, and freely rotatable 3D images were obtained for further analysis. Observed aneurysm remnants were electronically measured and classified for each modality by 2 experienced neuroradiologists. Results. Digital subtraction angiography and ivACT both provided high-quality images without motion artifacts. Artifact disturbances from the aneurysm clips led to a compromised, but still sufficient, image quality in 1 case. The ivACT assessed all aneurysm remnants as true-positive up to a minimal size of 2.6 x 2.4 mm in accordance with the DSA findings. There was a tendency for ivACT to overestimate the size of the aneurysm remnants. All cases without aneurysm remnants on DSA were scored correctly as true-negative by ivACT. Conclusions. By using an optimized image acquisition protocol as well as enhanced postprocessing algorithms, the noninvasive ivACT seems to achieve results comparable to those of conventional angiography in the follow-up of clipped cerebral aneurysms. The authors have shown that ivACT can provide reliable diagnostic information about potential aneurysm remnants after neurosurgical clipping with high sensitivity and specificity, sufficient for clinical decision making, at least for aneurysms in the anterior circulation located distal to the internal carotid artery. These preliminary results may be a promising step to replace conventional angiography by a noninvasive imaging technique in selected cases after aneurysm clipping.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Aneurysm clipping; Angiographic computed tomography; Follow-up imaging; Noninvasive imaging; Vascular disorders

Personalized computed tomography - Automated estimation of height and weight of a simulated digital twin using a 3D camera and artificial intelligence - Geißler, Frederik; Heiß, Rafael; Kopp, Markus; Wiesmüller, Marco; Saake, Marc; Wüst, Wolfgang; Wimmer, Andreas; Prell, Veronika; Uder, Michael; May, Matthias (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose The aim of this study was to develop an algorithm for automated estimation of patient height and weight during computed tomography (CT) and to evaluate its accuracy in everyday clinical practice. Materials and methods Depth images of 200 patients were recorded with a 3D camera mounted above the patient table of a CT scanner. Reference values were obtained using a calibrated scale and a measuring tape to train a machine learning algorithm that fits a patient avatar into the recorded patient surface data. The resulting algorithm was prospectively used on 101 patients in clinical practice and the results were compared to the reference values and to estimates by the patient himself, the radiographer and the radiologist. The body mass index was calculated from the collected values for each patient using the WHO formula. A tolerance level of 5kg was defined in order to evaluate the impact on weight-dependent contrast agent dosage in abdominal CT. Results Differences between values for height, weight and BMI were non-significant over all assessments (p > 0.83). The most accurate values for weight were obtained from the patient information (R2=0.99) followed by the automated estimation via 3D camera (R2=0.89). Estimates by medical staff were considerably less precise (radiologist: R2=0.78, radiographer: R2=0.77). A body-weight dependent dosage of contrast agent using the automated estimations matched the dosage using the reference measurements in 65 % of the cases. The dosage based on the medical staff estimates would have matched in 49 % of the cases. Conclusion Automated estimation of height and weight using a digital twin model from 3D camera acquisitions provide a high precision for protocol design in computer tomography. Key points: Machine learning can calculate patient-avatars from 3D camera acquisitions. Height and weight of the digital twins are comparable to real measurements of the patients. Estimations by medical staff are less precise. The values can be used for calculation of contrast agent dosage. Citation Format Geissler F, Heiβ R, Kopp M et al. Personalized computed tomography - Automated estimation of height and weight of a simulated digital twin using a 3D camera and artificial intelligence. Fortschr Röntgenstr 2021; 193: 437-445.
CRIS-Team Scopus Importer:2021-04-09
Keywords: 3D camera; automatic data collection; CT; digital twin; machine learning

Predicting the response of uveal melanoma to immunotherapy with MRI assessments - Moreira, Alvaro; Saake, Marc; Schuler, Gerold; Heinzerling, Lucie (CANCER IMMUNOLOGY RESEARCH, 2019)
CRIS-Team WoS Importer:2021-10-18

Primary anterior cruciate ligament repair-morphological and quantitative assessment by 7-T MRI and clinical outcome after 1.5 years. - Pachowsky, Milena; Söllner, Stefan; Gelse, Kolja; Sambale, Jannik; Nagel, Armin Michael; Schett, Georg; Saake, Marc; Uder, Michael; Roemer, Frank; Heiß, Rafael (European Radiology, 2024)
OBJECTIVES: The purpose of this study was to assess morphological and quantitative changes of the anterior cruciate ligament (ACL) and cartilage after ACL repair. METHODS: 7T MRI of the knee was acquired in 31 patients 1.5 years after ACL repair and in 13 controls. Proton density-weighted images with fat saturation (PD-fs) were acquired to assess ACL width, signal intensity, elongation, and fraying. T2/T2* mapping was performed for assessment of ACL and cartilage. Segmentation of the ACL, femoral, and tibial cartilage was carried out at 12 ROIs. The outcome evaluation consisted of the Lysholm Knee Score and International Knee Documentation Committee (IKDC) subjective score and clinical examination. RESULTS: ACL showed a normal signal intensity in 96.8% and an increased width in 76.5% after repair. Fraying occurred in 22.6% without having an impact on the clinical outcome (Lysholm score: 90.39 ± 9.75, p = 0.76 compared to controls). T2 analysis of the ACL revealed no difference between patients and controls (p = 0.74). Compared to controls, assessment of the femoral and tibial cartilage showed a significant increase of T2* times in all ROIs, except at the posterolateral femur. Patients presented a good outcome in clinical examination with a Lysholm score of 87.19 ± 14.89 and IKDC of 80.23 ± 16.84. CONCLUSION: T2 mapping results suggest that the tissue composition of the ACL after repair is similar to that of a native ACL after surgery, whereas the ACL exhibits an increased width. Fraying of the ACL can occur without having any impact on functional outcomes. T2* analysis revealed early degradation at the cartilage. CLINICAL RELEVANCE STATEMENT: MRI represents a noninvasive diagnostic tool for the morphological and compositional assessment of the anterior cruciate ligament after repair, whereas knowledge about post-surgical alterations is crucial for adequate imaging interpretation. KEY POINTS: • There has been renewed interest in repairing the anterior cruciate ligament with a proximally torn ligament. • T2 times of the anterior cruciate ligament do not differ between anterior cruciate ligament repair patients and controls. • T2 mapping may serve as a surrogate for the evaluation of the anterior cruciate ligament after repair.
EVALuna2:554516

Prior-based automatic segmentation of the carotid artery lumen in TOF MRA (PASCAL) - Hutter, Jana; Hofmann, Hannes; Grimm, Robert; Greiser, Andreas; Saake, Marc; Hornegger, Joachim; Dörfler, Arnd; Schmitt, Peter (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2012)
In current clinical practice, examinations of the carotid artery bifurcation are commonly carried out with Computed Tomography Angiography (CTA) or contrast-enhanced Magnetic Resonance Angiography (ceMRA). Quantitative information about vessel morphology, extracted from segmentations, is promising for diagnosis of vessel pathologies. However, both above-mentioned techniques require the administration of contrast media. In contrary, non-ce MRA methods such as Time-of-Flight (TOF) provide fully non-invasive imaging without any exogenous contrast agent. The diagnostic value of TOF MRA, however, for assessment of the carotid bifurcation area can be hampered due to its susceptibility to irregular blood flow patterns. Conventional methods for lumen segmentation are very sensitive to such signal voids and produce inaccurate results. In this work, a novel, fully automatic 3D segmentation algorithm is proposed which uses prior knowledge about irregular flow patterns. The presented technique has been successfully tested on eleven volunteer datasets as well as in a patient case, offering the comparison to CTA images. The sensitivity could be increased by 29.2% to 85.6% compared to standard level set methods. The root mean squared error in diameter measurements was reduced from 4.85mm to 1.44 mm.
CRIS-Team Scopus Importer:2022-08-05

Relevance of lesion size in navigator-triggered and free-breathing diffusion-weighted liver MRI - Reithmeier, Bianca; Laun, Frederik Bernd; Führes, Tobit; Uder, Michael; Bickelhaupt, Sebastian; Saake, Marc (European Radiology, 2024)
Objectives: The purpose of this study was to investigate the relevance of focal liver lesions (FLL) size for lesion detection comparing navigator triggering (TRIG) to free breathing (FB) liver Diffusion-weighted magnetic resonance imaging (DWI). Materials and method: Patients with known or suspected FLL were prospectively (registry number 276_19 B) included from October to December 2019 in this study, out of which 32 had liver lesions. Echo planar spin-echo DWI data both with TRIG and FB were with approximately constant acquisition times acquired at 1.5 T. Lesions were segmented in the b = 800 s/mm² images in both the TRIG and FB images. The lesion size, location (liver segment), liver lesion visibility, as well as contrast-to-noise ratio (CNR) were recorded. The CNR was assessed with the Wilcoxon–Mann–Whitney test and the number of visible lesions with the Fisher test. Results: Data from 43 patients (22 female) were analyzed. The mean patient age was 58 ± 14 years. A total of 885 FLL (Ntotal) were segmented. Among these, 811 lesions (Nboth) were detected with TRIG and FB, 65 lesions exclusively with TRIG (NTRIG_Only), and nine exclusively in FB (NFB_Only). The largest additional lesion in TRIG/FB had a diameter of 10.4 mm/7.6 mm. The number of additional lesions detected with TRIG decreased with size. Among all lesions ≤ 4.7 mm, the relative number of additional lesions was 15.6%. Additional lesions were found in all liver segments with TRIG. In the left liver lobe, the relative proportion was 9.2%, and in the right liver lobe 5.4%. CNR and visibility were significantly higher in TRIG than in FB (p < 0.001). In relation to size, the difference is significant in terms of visibility and CNR for lesion diameters ≤ 8 mm. Conclusion: Respiration triggering can improve the detection of small liver lesions with diameters up to approx. 1 cm in the whole liver. Key Points: Question Can respiration triggering (TRIG) improve the detection of small FLL compared to FB diffusion-weighted imaging? Findings Among 885 segmented FLL, TRIG was superior to FB for lesions smaller than 8 mm and had improved CNR and visibility. Clinical relevance Diffusion-weighted magnetic resonance imaging is used for the detection of focal liver lesions and image quality is influenced by breathing motion. Navigator triggering becomes more important for smaller lesions, and seems recommendable for the detection of small focal liver lesions.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Diffusion magnetic resonance imaging; Echo-planar imaging; Liver; Magnetic resonance imaging; Respiratory-gated imaging techniques

Single source split filter dual energy: Image quality and liver lesion detection in abdominal CT - Eichler, Mathis; May, Matthias; Wiesmüller, Marco; Saake, Marc; Heiß, Rafael; Uder, Michael; Wüst, Wolfgang (European Journal of Radiology, 2020)
Purpose: Aim of this study was to evaluate image quality of single source dual energy CT (SSDE-CT) using split filter technique in oncologic abdominal CT. Method: 51 consecutive patients with newly diagnosed breast carcinoma were prospectively enrolled in this study and underwent a staging examination of the abdomen using SSDE-CT (120 kV, split filter technique, 400 ref. mAs). Inline default images (DI) and post-processed virtual monoenergetic images at 40 keV, 50 keV, 60 keV, 70 keV and 80 keV were reconstructed. Objective image quality was evaluated as contrast to noise ratio (CNR) for liver parenchyma, portal vein, spleen, pancreas, aorta and hypoattenuating liver lesions. Subjective image quality was rated on a 5-point scale. Image quality at different keV settings was analyzed in paired t-tests. Results: CNR was highest at 40 keV for vessels (portal vein: 9.0, aorta: 8.8, all p < 0.001) and for upper abdominal organs (spleen: 4.8, all p < 0.001; pancreas: 2.7, all p < 0.01 except p = 0.93 for 50 keV; liver parenchyma: 3.4, all p < 0.01). Highest CNR values for hypoattenuating liver lesions were found at 40 keV (7.7, all p < 0.001). Overall subjective image quality was highest with 80 keV and DI (both 4.8, all p < 0.001). Artifacts were most pronounced at 40 keV. Conclusions: High image quality can be obtained with SSDE-CT of the abdomen. Lowest monoenergetic reconstructions provide the highest image contrast and should be used for vessel evaluation. The best trade-off between artifacts and parenchymal contrast can be obtained with 80 keV images.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Abdominal imaging; Breast carcinoma; Single source dual energy

Stereotactic vacuum-assisted breast biopsy (VABB)–a patients' survey - Eller, Achim; Janka, Rolf Matthias; Lux, Michael P.; Saake, Marc; Schulz-Wendtland, Rüdiger; Uder, Michael; Wenkel, Evelyn (Anticancer Research, 2014)
To analyze how patients experience Stereotactic guided vacuum-assisted breast biopsy (VABB) both physically and mentally.Two hundred and eleven consecutive women underwent VABB using one of two different biopsy devices (ATEC® and Mammotome®). Patients were queried using a questionnaire.One hundred and eighty-nine patients were included. 90% would again prefer VABB over a surgical biopsy. Average grading for the condition during the procedure was 2.5 (very good to good) and 2.1 (very good) for the condition the week following VABB. Minor complications were mentioned in 37%. (>90% pain and hematoma). 97% of the women were satisfied by the cosmetic results. Patients with malignant histology and younger age experienced the procedure significantly worse. A significant higher rate of minor complications was found in younger patients and in the ATEC® group.VABB is a physical and mental stressor to the women. Nonetheless, the majority of women indeed prefer the VABB.
EVALuna2:14365

The Art of Making Moulages - a hidden Art? - Sticherling, Michael; Groenhardt, K.; Saake, Marc (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

Thoracic non-osseous lesions in cancer patients detected in low-dose CT images acquired as part of skeletal SPECT/CT examinations - Wüst, Wolfgang; Lell, Michael; May, Matthias; Saake, Marc; Kuwert, Torsten; Uder, Michael; Linke, Rainer (Nuklearmedizin-Nuclear Medicine, 2015)
Hybrid single-photon emission tomographic (SPECT) and X-ray computed tomography (CT) systems are increasingly used in oncologic imaging. With SPECT/CT not only the thoracic spine but also the surrounding soft tissue needs to be evaluated for pathological findings. The purpose of this study was to assess the prevalence of non-osseous findings detectable on low-dose CT datasets from patients studied by thoracic 99mTc-dicarboxypropane diphosphonate (DPD)-SPECT/CT.119 consecutive oncologic patients (81 breast cancer, 38 with other cancer) who underwent DPD-SPECT CT of the thoracic region were included in this study. Non-osseous findings on CT were classified as either probably benign or suspicious. Suspicious findings were correlated with retrievable previous imaging and if performed with follow up imaging (MRI, CT with contrast medium, Ultrasound) or biopsy results.In 80/119 (67%) patients no imaging was performed before SPECT/CT. Only 7/119 subjects (6%) had no other lesions than bone lesions. In 101/119 (85%) patients lesions found on SPECT/CT images were rated as benign and in 65/119 (55%) patients as suspicious. In 8/119 (7%) patients with previously unknown suspicious lesions on SPECT/CT images suspicious findings were confirmed by biopsy.7% of patients referred to SPECT/CT of the thoracic spine for staging of malignant disease had previously unknown suspicious non-osseous lesions detectable on the low-dose CT images which were confirmed by biopsy. This could be especially relevant for cancer entities like breast and prostate, in which no thorax-CT is routinely intended for staging.
EVALuna2:13854

Variable White Matter Atrophy and Intellectual Development in a Family With X-linked Creatine Transporter Deficiency Despite Genotypic Homogeneity - Heussinger, Nicole; Saake, Marc; Mennecke, Angelika; Dörr, Helmuth-Günther; Trollmann, Regina (Pediatric Neurology, 2017)
The X-linked creatine transporter deficiency (CRTD) caused by an SLC6A8 mutation represents the second most common cause of X-linked intellectual disability. The clinical phenotype ranges from mild to severe intellectual disability, epilepsy, short stature, poor language skills, and autism spectrum disorders. The objective of this study was to investigate phenotypic variability in the context of genotype, cerebral creatine concentration, and volumetric analysis in a family with CRTD.The clinical phenotype and manifestations of epilepsy were assessed in a Caucasian family with CRTD. DNA sequencing and creatine metabolism analysis confirmed the diagnosis. Cerebral magnetic resonance imaging (cMRI) with voxel-based morphometry and magnetic resonance spectroscopy was performed in all family members.An SLC6A8 missense mutation (c.1169C>T; p.Pro390Leu, exon 8) was detected in four of five individuals. Both male siblings were hemizygous, the mother and the affected sister heterozygous for the mutation. Structural cMRI was normal, whereas voxel-based morphometry analysis showed reduced white matter volume below the first percentile of the reference population of 290 subjects in the more severely affected boy compared with family members and controls. Normalized creatine concentration differed significantly between the individuals (P < 0.005).There is a broad phenotypic variability in CRTD even in family members with the same mutation. Differences in mental development could be related to atrophy of the subcortical white matter.
EVALuna2:14646

VEXAS syndrome mimicking lupus-like disease - Valor-Mendez, Larissa; Sticherling, Michael; Zeschick, Martin; Atreya, Raja; Schmidt, Daniela; Waldfahrer, Frank; Saake, Marc; Hüffmeier, Ulrike; Schett, Georg; Rech, Jürgen (Rheumatology, 2023)
CRIS-Team WoS Importer:2023-03-17